Sustainability and innovation across the aquaculture value chain - Aarstad, Jarle; Jakobsen, Stig-Erik; Fløysand, Arnt; Kvitastein, Olav Andreas (Frontiers in Aquaculture, 2024)
Previous research has shown that Norwegian aquaculture firms strongly emphasize environmental and social sustainability, and this study aims to assess if the pattern is consistent across the value chain and consistent independent of suppliers’ amount of sales to fish farming. Also, it studies if value chain position and sales to fish farming are associated with innovation activities. Empirically, the study compares survey data between firms in the aquaculture industry and other industries as reference groups. The results show that aquaculture firms across the value chain overall emphasize environmental and social sustainability more than actors in the reference industries. For suppliers, the emphasis is strongest for those with high sales to fish farming. Another finding is that aquaculture firms’ innovation activities are relatively strong among firms providing services and input factors, particularly among suppliers with high sales to fish farming.